Study on Energy Consumption For Soybean-Sauce Production 'Pabrik Kecap Zebra' Ciampea, Bogor - . Sonhaji; Armansyah H. Tambunan (Jurnal Keteknikan Pertanian, 1999)
Energy is an Important factor for the success of industrialitation. and energy consumption of an industry. especially the small and medium industry. should be optimized based on the energy efficiency system. The objective of this research is to analyse the energy consumption for soybean sauce production at 'Pabrik Kecap Zebra'. Ciampea Bogor. and to evaluate the efficiency of stoves used at the industry.